Approaching Mrs. Slipslop, Uncle Toby and Mr. Bounderby from a Modern Individual Psychology Perspective - Mutlib, Yasir (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The paper examines the psychological superiority/inferiority complexes coined by Alfred Adler (1870-1937) in three selected characters from different novels: Mrs. Slipslop from Fielding’s Joseph Andrews (1742), Uncle Toby from Laurence Sterne’s Tristram Shandy (1759) and Mr. Bounderby from Dickens’s Hard Times (1854). These complexes are traced in the characters and associated with how they are induced by the characters’ physical and social deformities. The paper attempts to demonstrate that such psychological complexes in the character make it difficult for him/her to communicate as well as interact with others around them. Such deformities become whimsical obsessions that alienate them from their society and disorder their lives particularly at communication and result in impossibility of mutual understanding. The paper also highlights such complexes on the linguistic level.